Penerapan Pembelajaran Pendidikan Agama Islam Berbasis Higher Order Thinking Skill (HOTS) di SMA Negeri Jogoroto - Chintya Nur Alfaizinun; Emi Lilawati (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
The formation of student character can be achieved through the application of Higher Order Thinking Skills (HOTS) learning. HOTS is the ability to think at a higher level to describe, conclude, and analyze in solving an unpredictable problem. This study aims to: 1) Know the implementation of HOTS in PAI for class XI students of SMA Negeri Jogoroto. 2) Knowing the obstacles in applying HOTS to PAI for class XI students of SMA Negeri Jogoroto. 3) Knowing the HOTS evaluation on PAI material for class XI students of Jogoroto State Senior High School. The method used in this research is descriptive qualitative research. The collection methods are observation, interviews, and documentation. The types and sources of data used are primary and secondary data by analyzing data validity techniques. The results of this study indicate the application of HOTS to PAI material which is carried out from the planning and implementation, the constraints, and the evaluation that is applied. As for the implementation of learning in fostering students' high-level thinking skills.